A Friend to Milli Mörriäinen : The Storification Method Supporting Pupils' Crafting Processes - Rönkkö, Marja-Leena (Nordic forum for Research and Development work in Educational Sloyd/Craft, 2025)
Arts-based and creative learning processes should be utilised more in craft education. With the NaCra approach, craft processes are connected to other creative content, mainly narratives. This NaCra study explored pupils' holistic craft processes that incorporated storified elements and the aim was to clarify the key elements of individual craft processes supported by storification. The study involved 12 pupils from the second grade (7–8 years old) in Finnish primary education. Despite the novelty of the holistic approach, all pupils successfully planned, created and evaluated their soft toys. The storification method permeated every stage of the holistic craft process, aiding not only the ideation and design phases but also motivation and increased concentration in the making and evaluation phases. The findings suggest that pupils' holistic craft processes incorporating storified elements work well together as a means for pupils to express their thoughts and imagination into assignments. Furthermore, storified elements make pupils' experiences come to life in the creative crafting process. Pupils should have more opportunities with holistic craft processes where the outcome is uncertain at the beginning of the process.